Effect of cutting speed on Bio-corrosion of AISI 316L stainless steel - Saliza Azlina, O.; Kamarul Ariffin, C.; Ibrahim, M.; Kurniawan, Denni (Asian Research Publishing Network (A R P N), 2016)
Stainless steel of AISI 316L type (SS316L) has been widely used as metallic biomedical implants material because of it offers good characteristics, including high mechanical properties and biocompatibility, and relatively low cost. However, its machinability an issue, with relation between cutting parameters and surface roughness is of interest to be considered. Related to this, its corrosion behavior related to cutting parameters also needs to be taken into consideration due to its application in implants. This study investigates the biocorrosion behavior of AISI 316L stainless steel which was machined by face milling at different cutting speeds. The cutting speeds were 100, 300 and 500 m/min while feed rate and depth of cut was kept constant. Initial assessment was done on the surface roughness of the face milled samples, with initial hypothesis that the surface roughness should be constant for all cutting speeds, with Ra to be within 0.8 - 1.2 µm. Biocorrosion test was then performed on the samples by Potentiodynamic Polarization Test under a simulated body fluid (SBF) electrolyte. It was found that although similar surface roughness is expected, the cutting speed affected the surface roughness in which the surface roughness tended to be inversely proportional to the cutting speed. Samples machined at the highest cutting speed was observed to have smooth surface with less defects, such as pits and grooves, compared to samples machined at lower cutting speeds. Related to this, the corrosion behavior of the AISI 316L stainless steel was also affected by the cutting speed during its face milling where the corrosion rate is inversely proportional to the cutting speed.